Pengaruh Keselamatan Kerja dan Kesehatan Kerja terhadap Produktivitas Karyawan PT Gubah Tiara Perkasa Surabaya - Mohammad Faisal; Iswati Iswati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Currently, many PT Gubah Tiara Perkasa employees, especially LPG gas filling operators, lack awareness of the dangers in the workplace, such as not using personal protective equipment which can result in injury if an incident occurs at the work site. This research was conducted at PT Gubah Tiara Perkasa which is located in the city of Surabaya. The purpose of this research is to determine and analyze the influence of the Occupational Safety and Health (K3) program on the productivity of production employees at PT Gubah Tiara Perkasa, Surabaya City. The type of research used is explanatory research with a quantitative approach. In this research, the population is 40 Production Employees at PT Gubah Tiara Perkasa, Surabaya City. The data collection technique used was a questionnaire. The data analysis used is multiple linear regression analysis. Based on research, it was found that the Occupational Safety and Occupational Health (K3) program had an effect on the work productivity of production employees at PT Gubah Tiara Perkasa.